An Analysis of Evaluation for Korean Native Cattle (Hanwoo) Reproductive Performance and Cow-Calf Profitability - Jaesung Cho; Changhee Do; Hyungjun Song; Inchul Choi (The Korean Society of Animal Reproduction and Biotechnology, 2015)
Calculating break-even price of calf production is closely associated with reproductive efficiency. To determine the price, we need data from reproduction records including number of claves weaned, number of cows exposed for breeding, and annual cash coast per cow, and average weaning or market weight of claves sold and retained. Unfortunately, the data were not available in Korea native cow (Hanwoo). To evaluate the performance and the price, we collected calving interval from about 60,000 cows for last 10 years and estimated reproductive performance. Calving interval was increased 4.3% and pregnancy rate was decreased about 1.4 ~ 2.8% year-on-year. Increases in growth rates of number of cow and semen per calf supported the low reproductive performance. Finally, break-even price was calculated using estimated percent calf crop and demonstrated that growth rate of break-even price is larger than that of annual cash per cow, suggesting cow-calf profitability and financial efficiency in Korea native cow (Hanwoo) is getting worse.